Major Topics of the Hadith - Lucas, Scott C. (Religion compass, 2008)
Hadiths - reports of what the Prophet Muhammad said, did, or tacitly approved - have exerted an extraordinary influence on Muslims for over a millennium. Despite the significance of this literature, its contents remain largely inaccessible to non-Arabic readers, in part due to many Western scholars’ preoccupation with the question of its authenticity rather than the function of hadith in Islamic thought. This article provides an overview of the contents of the canonical Sunni hadith collections along with a sample of ethical hadiths in idiomatic English.